Cash for Conservation? The Environmental State, Public Payment for Ecosystem Services Programs, and Forest Loss in Low- and Middle-Income Nations - Marion C. Harper; Laura McKinney; Michael Restivo; John M. Shandra; Jamie M. Sommer (Socius)
The authors draw on environmental state theory to inform this study, examining the relationship between public payment for ecosystem services programs and forest loss from 2001 to 2015 in low- and middle-income nations. The authors analyze data for a sample of 79 low- and middle-income nations using a two-stage fractional regression model to address the potential issue of endogeneity on the public payment for ecosystem services program measures. The authors find support for environmental state theory that higher levels of payments to users as part of public payment for ecosystem services programs correspond to less forest loss in low- and middle-income nations. The authors also find that a composite variable, which measures key characteristics that may enhance the effectiveness of public payment for ecosystem services programs, has a similar relationship with forest loss in low- and middle-income nations. The authors conclude by discussing the theoretical, methodological, and policy implications of these findings.